2018
DOI: 10.1016/j.nmni.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and molecular characterization of Klebsiella spp. isolates causing community-acquired infections

Abstract: Klebsiella spp. isolates from community-acquired infections were characterized. A total of 39 Klebsiella spp. isolates were obtained from outpatients at four rural hospitals in Mexico (2013–2014). The biochemical tests identified all as being K. pneumoniae. The molecular multiplex-PCR test identified 36 (92.4%) K. pneumoniae isolates and one (2.5%) K. variicola isolate, and phylogenetic analysis of the rpoB gene identified two isolates (5.1%) belonging to K. quasipneumoniae subsp. quasipneumoniae and K. quasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 39 publications
7
32
2
1
Order By: Relevance
“…For this reason, future comparative studies should include K. pneumoniae strains from other clinical origins to further understand the role of dogs as reservoirs of pathogenic K. pneumoniae. In fact, the K. pneumoniae clonal lineages detected in dogs from this study have been previously isolated from several types of human infections besides UTI (39,(42)(43)(44).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…For this reason, future comparative studies should include K. pneumoniae strains from other clinical origins to further understand the role of dogs as reservoirs of pathogenic K. pneumoniae. In fact, the K. pneumoniae clonal lineages detected in dogs from this study have been previously isolated from several types of human infections besides UTI (39,(42)(43)(44).…”
Section: Discussionmentioning
confidence: 74%
“…The detection of a high-risk K. pneumoniae clonal lineage colonizing a healthy dog highlights its possible role as a reservoir. Furthermore, other K. pneumoniae clonal lineages that were detected in dogs, namely ST188, ST252, ST281, ST423, and ST1093, have also been previously implicated in human infections (39,(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Hasan et al (2014) described a clonal expansion of CC147 by Verone integron-encoded metallo-beta-lactamase (VIM)-producing K. pneumoniae strains isolated from Greece. ST392 has been reported worldwide as an emergent clone associated with the spreading KPC-producing K. pneumoniae (Yang et al, 2013; Di Mento et al, 2018; Garza-Ramos et al, 2018). In Brazil, ST392 was previously reported in a KPC-2-producing K. pneumoniae harboring the mcr- 1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, similarly to MRSA, in community-acquired Klebsiella infections the more virulent and less resistant strains of "nonmajor ST" K. pneumoniae will dominate, like ST23 and ST65 (Zhao et al, 2016;Chen Y.T. et al, 2017;Garza-Ramos et al, 2018;Shi et al, 2018) in which high-level resistance to fluoroquinolones has not been reported to date.…”
Section: The Virulence Component In Mdr K Pneumoniaementioning
confidence: 99%